The genus Campylomma Reuter, 1878 (Hemiptera: Heteroptera: Miridae: Phylinae): two new synonyms and discussion of the diagnosis - Konstantinov, Fedor V.; Neimorovets, Vladimir V.; Korzeev, Andrei I. (Zootaxa, 2015)
The diagnostic characters of the phyline plant bug genus Campylomma Reuter, 1878 are discussed based on examination of Western Palearctic species. Nigrocapillocoris Wagner, 1973 is synonymized with Campylomma and Campylomma celatum Wagner, 1969 is synonymized with C. annulicorne (Signoret, 1865). Illustrations of the male genitalia, photographs of the dorsal habitus, micrographs of selected structures are given for discussed species and a redescription of C. ochraceum (Scott, 1872) comb. nov. is provided.